The Relationship between Second-to-Fourth Digit Ratios, Attention-Deficit/Hyperactivity Disorder Symptoms, Aggression, and Intelligence Levels in Boys with Attention-Deficit/Hyperactivity Disorder - Işık, Ümit (Psychiatry Investig, 2020)
OBJECTIVE: Observations of sex differences have led some scientists to doubt whether the neuroendocrine system is involved in attentiondeficit/hyperactivity disorder (ADHD) etiology. One of the interesting study subjects in this context is prenatal steroid hormone exposure. The aim of the present study was to replicate and extend previous work by addressing two research questions: 1) Are second-to-fourth digit (2D:4D) ratios lower in ADHD than in controls? 2) Is there a correlation between 2D:4D ratios and symptoms of ADHD, aggression and intelligence scores in boys with ADHD? METHODS: The study included 100 treatment-naive male children diagnosed with ADHD and 55 healthy male children. We measured the ratios of 2D:4D and administered a Wechsler Intelligence Scale for Children-Revised to assess IQ scores, as well as behavioral rating scales, in children with ADHD and comparison individuals. RESULTS: We observed lower 2D:4D ratios in the right hand in ADHD in comparison to the control group. The left-hand ratios of 2D:4D, however, did not differ between ADHD and control groups. There were negative correlations between the left-hand 2D:4D ratios and the hyperactivity scores. However, no significant correlation was detected between right-hand 2D:4D ratios and the psychological questionnaire scores. CONCLUSION: These results provide further evidence that fetal androgen exposure may contribute to the pathophysiology of ADHD, at least in boys.